Mechanical characterization of ABS recyling based electric and electronic equipment (WEEE) by using injection molding - Mat Hassan, Nik Normunira; M. Rus, Anika Zafiah; Saleh, Aslinda; Marsi, Noraini; Mohamed Yusop, Fatimah; Samiran, Norafzanizam; Sulong, Nurulsaidatulsyida; Tuan Ismal, Tuan Noor Hasanah; Mohammad Noor, Hafsa (Penerbit UTHM, 2020)
Nowadays, recycling process become more and more importantly mostly due to the impressive increase in the production of waste and to growing attention to the environment friendly. Increasing of demand of new products and waste electric and electronic of waste polymer from many sectors is being recycled to reduce an economic, environment and energy issues. According to Rosa et al., (2010) and Tarantili et al., (2010), the term of polymer usually refers to thermoplastic material rather than thermosets and some typical representative’s acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonates (PC), polyamides (PA) and poly (ethylene terephthalate) (PET).